Analysis of The Ability to Understand Mathematical Concepts of High School Students in Class X on Vector Material - Urni Babys; Netty J. Marlin Gella; Mario Dos Santos Amaral (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The purpose of this study is to produce a study of the ability to understand mathematical concepts of Class X students on Vector material. This study uses a qualitative approach with a descriptive type of research. The subjects of this study were students of Class X MIA2 Christian High School 2 Soe even semester of the 2021/2022 school year as many as 30 people. Data collection techniques using mathematical concept comprehension ability tests, semi-structured interviews, and documentation. The data analysis technique follows the Miles and Huberman model with a validity test of data using the triangulation technique. The results showed that that the ability to understand mathematical concepts of students is still relatively low with the median age being 55.56%. The results of the Student Work analysis showed that there were students who did not understand the concept and used it in solving problems, students who mistakenly in choosing and applied algorithms, incorrectly restated concepts, and associated various mathematical concepts internally and externally. Some students are also still in a hurry to work on the problem, less thorough reading and understanding of the problem, resulting in students making mistakes in solving the problem